Passive daylighting in public higher educational buildings: retrofitting strategies and process frameworks for sustainable spaces / Muhammad Anas Othman - Othman, Muhammad Anas (2024)
The escalating global focus on green and sustainable development has seen an increased emphasis on the role of the built environment in reducing energy use and environmental impact. This is particularly evident in Higher Education Institutions (HEIs), where buildings are known to be substantial energy consumers, primarily in terms of electricity. One of the key drivers of this heavy electricity usage is the inadequate implementation of passive daylighting strategies. To address this, the 11th Malaysia Plan spotlights the need to retrofit existing government buildings with a focus on energy efficiency and low-carbon emissions by employing passive daylighting strategies. The emphasis on retrofitting implies a need for further exploration of effective strategies, especially those relating to daylighting. This research addresses this requirement, aiming to establish a process framework for retrofitting design using daylight passive strategies to reduce energy waste and achieve sustainable spaces HEIs buildings.